Electrocardiographic signs of atrial myopathy in patients with rheumatoid arthritis: results from the multicenter prospective EDRA study. (3rd October 2022) - Sanna, G D; Piga, A; Ponti, E; Falco, O; Piga, M; Casu, G; De Luca, G; Erre, G L
Abstract: Background: Atrial myopathy is a complex condition due to a variety of causes resulting in mechanical and/or electrical remodeling and dysfunction. This can lead to arrhythmias (e.g. atrial fibrillation – AF) and/or heart failure (HF) symptoms. Surface 12-lead electrocardiogram (ECG) may provide the first clues about the presence of left atrial (LA) abnormalities. Interatrial blocks (IAB, partial – pIAB or advanced - aIAB) and abnormal P wave terminal force in lead V1 (aPtfV1) are recognized markers of electromechanical LA dysfunction. Chronic systemic inflammatory diseases are associated with increased cardiovascular risk. An increased incidence of AF has been reported in patients with rheumatoid arthritis (RA). However, the role of ECG with its markers of atrial myopathy in the context of RA have been never investigated so far. Purpose: This observational cross-sectional study aimed to investigate: 1) the prevalence of ECG signs of atrial myopathy in RA and to compare it with that found in a selected cohort of control subjects; and 2) to assess the independent determinants of the presence of ECG features of atrial myopathy. Methods: Two-hundred and eighteen patients with RA and 109 controls matched by age, gender and overall cardiovascular-risk profile underwent clinical evaluation and 12-lead ECG. The presence of IAB and or aPtfV1 was carefully investigated in all the ECG tracings. Patients with previous cardiovascular diseases and atrial fibrillation were excluded from the present study. Results: Mean duration of the P wave on ECG was significantly longer in patients with RA than in controls (118±12 msec vs 112±10 msec, p<0.001). Similarly, pIAB was present in 43% of RA patients vs 21% of controls (p<0.001). The presence of aIAB was a rare finding being present only in 2 patients with RA. An abnormal PtfV1 was more frequently found in RA (27% vs 10%, p<0.001). Overall ECG features of atrial myopathy (i.e. aIAB or pIAB + abnormal PtfV1) were highly prevalent (15% vs 4%, p=0.003) in the RA group. There was a higher percentage of males in the subgroup of patients with RA and atrial myopathy (50% vs 28%, p=0.013). We did not find any relationship between RA disease duration and ECG features of atrial myopathy. On multivariate regression analysis male gender (OR [95% CI] = 3.07 [1.47–6.41], p=0.003) and RA (OR [95% CI] = 4.76 [1.51–14.4], p=0.006) were the only independent predictors of the presence of atrial myopathy on ECG. Conclusions: ECG signs of atrial myopathy are highly prevalent in patients with RA compared to controls. A low-cost and easily available tool such as surface 12-lead ECG should be used in RA for the investigation and possibly early identification of LA myopathy. Further studies with advanced imaging techniques and specific laboratory markers could confirm these preliminary findings and help clarify the underlying pathophysiological mechanisms and the clinical correlates. Funding Acknowledgement: Type of funding sources: None.